Deactivation of metastable single-crystal silicon hyperdoped with sulfur - Simmons, C. B.; Akey, Austin J.; Krich, Jacob J.; Sullivan, Joseph T.; Recht, Daniel; Aziz, Michael J.; Buonassisi, Tonio (Journal of applied physics, 2013)
Silicon supersaturated with sulfur by ion implantation and pulsed laser melting exhibits broadband optical absorption of photons with energies less than silicon's band gap. However, this metastable, hyperdoped material loses its ability to absorb sub-band gap light after subsequent thermal treatment. We explore this deactivation process through optical absorption and electronic transport measurements of sulfur-hyperdoped silicon subject to anneals at a range of durations and temperatures. The deactivation process is well described by the Johnson-Mehl-Avrami-Kolmogorov framework for the diffusion-mediated transformation of a metastable supersaturated solid solution, and we find that this transformation is characterized by an apparent activation energy of EA=1.7 ± 0.1 eV. Using this activation energy, the evolution of the optical and electronic properties for all anneal duration-temperature combinations collapse onto distinct curves as a function of the extent of reaction. We provide a mechanistic interpretation of this deactivation based on short-range thermally activated atomic movements of the dopants to form sulfur complexes.